1960
DOI: 10.1111/j.1476-5381.1960.tb01261.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adrenaline and Noradrenaline on the Metabolism and Performance of the Isolated Dog Heart

Abstract: In 16 dog heart-lung preparations modified to permit a more accurate measurement of coronary flow, adrenaline or noradrenaline was infused at a rate of 4 ,ug. base/min. After a 30-mmn. pause during which the increased oxygen consumption and heart rate, but not the coronary flow, returned to pre-infusion levels, the other sympathomimetic amine was infused for the same length of time. It was found that, mole per mole, noradrenaline is as effective, and probably more so, than adrenaline in raising the oxygen cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1961
1961
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Pletscher (1961) noted an increase in the blood pyruvate and lactate levels when monoamine oxidase inhibitors were given to human subjects. Fawaz & Tutunji (1960) also found that adrenaline and noradrenaline were approximately equal in their effect on the oxygen consumption of the dog heart-lung preparation. In the work described in this paper, both these amines depressed the recovery of contraction when present in the anoxic phase.…”
Section: The Effect Of Iproniazidmentioning
confidence: 88%
“…Pletscher (1961) noted an increase in the blood pyruvate and lactate levels when monoamine oxidase inhibitors were given to human subjects. Fawaz & Tutunji (1960) also found that adrenaline and noradrenaline were approximately equal in their effect on the oxygen consumption of the dog heart-lung preparation. In the work described in this paper, both these amines depressed the recovery of contraction when present in the anoxic phase.…”
Section: The Effect Of Iproniazidmentioning
confidence: 88%
“…6 Nevertheless, when looking at the effects of norepinephrine on heart contractile performance, it appears as efficient as epinephrine. 13,14 Experimental data on isolated myocardial heart tissues have shown that norepinephrine is inotropic and lusitropic at low and high concentrations whereas epinephrine increases inotropism at low concentration and decreases the latter at high concentration. This is explained by a differing action on ␤-2 receptors because both Gs and Gi pathways are stimulated by epinephrine, whereas only Gs is stimulated by norepinephrine.…”
mentioning
confidence: 99%
“…Changes in heart rate together with changes in venous return, stroke volume and peripheral resistance might modify the true isotropic effect of catecholamines. Heart rate has not been controlled ordinarily in the in situ experiments (Crismon and Tainter 1938, Lands and Howard 1952, Goldberg et al 1953, Cotten and Pincus 1955, Fawaz and Tutunji 1960. It has been reported that isoproterenol exhibited the most potent isotropic effect among catecholamines in the rabbit (Lands and Howard 1952) and in the dog (Moran 1966).…”
Section: ) Frequency-force Relationship and Positive Inotropic Effecmentioning
confidence: 99%
“…The inotropic potencies of catecholamines, naturally occurring and synthetic, have been determined in various preparations of mammalian ventricular muscle, i.e., isolated papillary muscles (Garb 1950, Lee andYu 1964), heart-lung prepara tion (Crismon andTainter 1938, Fawaz andTutunji 1960) and hearts in situ (Goldberg et al 1953, Cotten and Pincus 1955, Moran 1966. While isoproterenol was found to be the most potent catecholamine (Lands andHoward 1952, Moran 1966), differences in potencies between epinephrine and norepinephrine occur among various species of animals.…”
mentioning
confidence: 99%